The cultural politics of sport mega-events - Lorenzo Pedrini; Simone Tosi (Eracle)
2024 has been the year of the XXXIII Summer Olympic Games. The Paris Games have catalysed the attention of millions of people all over the world, aroused mixed feelings, and triggered transformations whose effects could be fully grasped in the coming years. To coincide with the Olympic year, Eracle is pleased to dedicate the volume 7(1) to sports mega-events.